AUDIT ENERGI DAN ANALISA PELUANG HEMAT ENERGI PADA BANGUNAN GEDUNG PT. X - Derry Septian; Joko Prihartono; Purwo Subekti (Jurnal APTEK, 2013)
From the research that has been conducted on energy audits in buildings PT. X, to know the profile of energy use and energy savings opportunities, so it can be more efficient and save costs. From the initial energy audit have been implemented acquired Energy Consumption Intensity (IKE) to the total area is still under IKE standards for office buildings. For air-conditioned room is not air conditioned and acquired Energy Consumption Intensity (IKE) is low so as very efficient. By replacing energy-efficient appliances, then there is a chance of saving energy